Teaching Dispositional Optimism in the Entrepreneurial Classroom - Crane, Frederick G.; Meyer, Mark H. (Senate Hall, 2007)
This study demonstrates that dispositional optimism, a key trait found in successful entrepreneurs, can be effectively measured and enhanced in the entrepreneurial classroom. Undergraduate students with an expressed interest in entrepreneurship were given a Life Orientation Test (LOT-R) prior to attending any entrepreneurship classes. Then, over a semester-length course, the students were exposed to lectures, videos, readings, and guest speakers that dealt with the business skills necessary for entrepreneurial success as well as an explicit pedagogy focusing on the psychology of entrepreneurship, including dispositional optimism. A follow-up LOT-R was conducted at the end of the class semester. It revealed that students showed a statistically significant improvement in their dispositional optimism score. This finding has major implications in terms of curriculum design and pedagogical approaches to teaching entrepreneurship.
Keywords: dispositional optimism|entrepreneurs|teaching|classroom